Nursing supervision for care comprehensiveness - Lucieli Dias Pedreschi Chaves; Vivian Aline Mininel; Jaqueline Alcântara Marcelino da Silva; Larissa Roberta Alves; Maria Ferreira da Silva; Silvia Helena Henriques Camelo
ABSTRACT Objective: To reflect on nursing supervision as a management tool for care comprehensiveness by nurses, considering its potential and limits in the current scenario. Method: A reflective study based on discourse about nursing supervision, presenting theoretical and practical concepts and approaches. Results: Limits on the exercise of supervision are related to the organization of healthcare services based on the functional and clinical model of care, in addition to possible gaps in the nurse training process and work overload. Regarding the potential, researchers emphasize that supervision is a tool for coordinating care and management actions, which may favor care comprehensiveness, and stimulate positive attitudes toward cooperation and contribution within teams, co-responsibility, and educational development at work. Final considerations: Nursing supervision may help enhance care comprehensiveness by implying continuous reflection on including the dynamics of the healthcare work process and user needs in care networks.